2011
DOI: 10.1097/ccm.0b013e31820eabab
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hospital and intensive care unit length of stay*

Abstract: Case-mix-adjusted benchmarks for hospital and intensive care unit stays reveal substantial differences in unit efficiency. Hospital and intensive care unit stays are strongly correlated at the patient and unit level, suggesting that there are causal factors common to both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
1
25
1
1
Order By: Relevance
“…As opposed to the volume-outcome literature [70], mixed models would appear to have been have been applied in a relatively small number of studies for length of stay analysis [16,71-75]. The use of administrative data [5,16] may also be associated with integer based calendar–day recording which lacks the accuracy of fractional day based “exact” times [10,71]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As opposed to the volume-outcome literature [70], mixed models would appear to have been have been applied in a relatively small number of studies for length of stay analysis [16,71-75]. The use of administrative data [5,16] may also be associated with integer based calendar–day recording which lacks the accuracy of fractional day based “exact” times [10,71]. …”
Section: Discussionmentioning
confidence: 99%
“…Because of the non-normality of length of stay, formal trimming [76,77] or truncation [71,77,78] of the data, or deleting [5,73,79] “outliers” has been undertaken prior to possible data transformation. For instance, studies implementing the APACHE III [78] or IV [71] algorithms for predicting ICU length of stay have truncated the latter at 30 days, at a 1% data level; the same fraction as seen with data deletions [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital resource usage variables included ICU and hospital (non-ICU) lengths of stay. 38,39 Number of medical consultations was considered a resource usage variable to assess "human" resources and included allergy/immunology, anesthesiology, cardiology, head and neck, emergency medicine, family practice, infectious disease, internal medicine, neurology, neurosurgery, obstetrics and gynecology, oral and maxillofacial surgery, ophthalmology, orthopedics, otolaryngology, psychiatry, pulmonary, radiology, renal service, surgery (general, handorthopedics, thoracic, trauma, vascular), urology, and other. Number of procedures was included to assess human and material resources; all procedures performed during the course of care were included (eg, surgical, diagnostic).…”
Section: Study Variablesmentioning
confidence: 99%
“…A prolonged ICU stay can adversely affect one's health status by increasing the risk of infection, complications and, possibly, mortality [2,3]. It has been demonstrated that LOS in an ICU is affected by several medical, social, psychological and institutional factors [4].…”
Section: Length Of Stay (Los)mentioning
confidence: 99%